GENETIC ASSOCIATION BETWEEN ARTERIAL STIFFNESS-RELATED GENE POLYMORPHISMS IN BRVO AND CRVO PATIENTS IN A TURKISH POPULATION - Demir, Selim; Ortak, Hüseyin; Benli, İsmail; Alim, Sait; Bütün, İlknur; Güneş, Alper; Ateş, Ömer (Retina (Philadelphia, Pa.), 2015)
To investigate possible associations between five different single-nucleotide polymorphisms, from genes associated with arterial stiffness and branch retinal vein occlusion (BRVO), or central retinal vein occlusion. A total of 187 patients with retinal vein occlusion (133 with BRVO and 54 with central retinal vein occlusion), and 167 controls, were enrolled in this study. All subjects were screened for hypertension, diabetes, smoking status, body mass index, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, total cholesterol, and very low-density lipoprotein. The genotyping of adiponectin +276 G/T, ACE I/D, AGTR1 A1166C, eNOS E298D, and p22phox -242 C/T polymorphisms was performed using real-time polymerase chain reaction. The percentage of the adiponectin +275 T allele carriers was significantly higher in the BRVO patients (37%) than in the controls (23%, P < 0.001). Similarly, the percentage of AGTR1 1166 C allele carriers was significantly higher in the BRVO patients (38%) than in the controls (24%, P < 0.001). At the multiple logistic regression analysis, the adiponectin +275 T allele carrier and AGTR1 1166 C allele carrier status were found to be associated with an increased risk of BRVO (TT vs. GG and TG: odds ratio = 2.278, P = 0.002, 95% confidence interval: 1.370-3.789; CC vs. AA and AC: odds ratio = 1.804, P = 0.025, 95% confidence interval: 1.079-3.017). The genotype distributions or allelic frequencies of ACE I/D, eNOS E298D, and p22phox -242 C/T did not significantly differ between the patients with BRVO and the control subjects. There was no significant difference between the central retinal vein occlusion patients and controls for the genotype or the allele frequency distributions of all evaluated single-nucleotide polymorphisms. Adiponectin +276 G/T and AGTR1 A1166C single-nucleotide polymorphism are likely to be risk factors for BRVO.